1989
DOI: 10.1017/s0043174500055934
|View full text |Cite
|
Sign up to set email alerts
|

Quackgrass (Agropyron repens) Biotype Response to Sethoxydim and Haloxyfop

Abstract: Crown bud, tiller, and rhizome development was studied in 10 quackgrass biotypes at two stages (three-to four- and seven- to eight-leaf stages) of development to determine if differential development of these structures influenced control with sethoxydim and haloxyfop. There was a differential response among the 10 biotypes to both sethoxydim and haloxyfop at both stages of development. The biotypes differed in the number of crown buds, tillers, and rhizomes that formed at both stages of development. In the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Chao et al (1994) showed that apical dominance of wild oat (Avena fatua L.) inhibited translocation of imazamethabenz to crown buds. Quackgrass [Elytrigia repens (L.) Nevski] was also more difficult to control when greater numbers of crown buds were present (Alcantara et al 1989), and older buds received less translocated herbicide than younger buds (Shieh et al 1993). All herbicide treatments reduced OWB aerial reproductive tiller density compared with the control in 2001 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Chao et al (1994) showed that apical dominance of wild oat (Avena fatua L.) inhibited translocation of imazamethabenz to crown buds. Quackgrass [Elytrigia repens (L.) Nevski] was also more difficult to control when greater numbers of crown buds were present (Alcantara et al 1989), and older buds received less translocated herbicide than younger buds (Shieh et al 1993). All herbicide treatments reduced OWB aerial reproductive tiller density compared with the control in 2001 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Results of treatment made at older stages were contra dictory: Claus and Behrens (5) and Ivany (10) found no difference whereas Wallgren (19) reported a loss of efficacy at the five-to seven-leaf stage compared with the three-to five-leaf stage. With the APP and CHD herbicides, treatments made at the six-to eight-leaf stage of quackgrass resulted in less control compared with treatment on younger plants (1,4,11,15).…”
Section: Introductionmentioning
confidence: 99%
“…Quack grass biotypes differ in growth and development characteristics. Quackgrass biotypes or clones have exhibited differential re sponses to several herbicides including primisulfuron (1,2,7,8,17). Primisulfuron is a sulfonylurea herbicide registered for postemergence control of quackgrass and other weed species in com (Zea mays L.) at 40 g ha" 1 (3,5,6,9,10,13).…”
Section: Introductionmentioning
confidence: 99%